Garlic γ-glutamyl transpeptidases that catalyze deglutamylation of biosynthetic intermediate of alliin - Yoshimoto, Naoko; Yabe, Ayami; Sugino, Yuka; Murakami, Soichiro; Sai-ngam, Niti; Sumi, Shin-ichiro; Tsuneyoshi, Tadamitsu; Saito, Kazuki (Frontiers in Plant Science, 2015)
S-Alk(en)yl-L-cysteine sulfoxides are pharmaceutically important secondary metabolites produced by plants that belong to the genus Allium. Biosynthesis of S-alk(en)yl-L-cysteine sulfoxides is initiated by S-alk(en)ylation of glutathione, which is followed by the removal of glycyl and γ-glutamyl groups and S-oxygenation. However, most of the enzymes involved in the biosynthesis of S-alk(en)yl-L-cysteine sulfoxides in Allium plants have not been identified. In this study, we identified three genes, AsGGT1, AsGGT2, and AsGGT3, from garlic (Allium sativum) that encode γ-glutamyl transpeptidases catalyzing the removal of the γ-glutamyl moiety from a putative biosynthetic intermediate of S-allyl-L-cysteine sulfoxide (alliin). The recombinant proteins of AsGGT1, AsGGT2, and AsGGT3 exhibited considerable deglutamylation activity toward a putative alliin biosynthetic intermediate, γ-glutamyl-S-allyl-L-cysteine, whereas these proteins showed very low deglutamylation activity toward another possible alliin biosynthetic intermediate, γ-glutamyl-S-allyl-L-cysteine sulfoxide. The deglutamylation activities of AsGGT1, AsGGT2, and AsGGT3 toward γ-glutamyl-S-allyl-L-cysteine were elevated in the presence of the dipeptide glycylglycine as a γ-glutamyl acceptor substrate, although these proteins can act as hydrolases in the absence of a proper acceptor substrate, except water. The apparent Km values of AsGGT1, AsGGT2, and AsGGT3 for γ-glutamyl-S-allyl-L-cysteine were 86 μM, 1.1 mM, and 9.4 mM, respectively. Subcellular distribution of GFP-fusion proteins transiently expressed in onion cells suggested that AsGGT2 localizes in the vacuole, whereas AsGGT1 and AsGGT3 possess no apparent transit peptide for localization to intracellular organelles. The different kinetic properties and subcellular localizations of AsGGT1, AsGGT2, and AsGGT3 suggest that these three GGTs may contribute differently to the biosynthesis of alliin in garlic.